Epistemology, Context, and Formalism
X, 250 p. 16 illus.
Keywords: The main purpose of the present volume is to advance our understanding of the notions of knowledge and context, the connections between them, and the ways in which they can be modeled, in particular formalized – a question of prime importance and utmost relevance to such diverse disciplines as philosophy, linguistics, computer science and artificial intelligence, and cognitive science. Bringing together essays written by world-leading experts and emerging researchers in epistemology, logic, philosophy of language, linguistics, and theoretical computer science, the book examines the formal modeling of knowledge and the knowledge-context link at one or more of three intersections -- context and epistemology, epistemology and formalism, formalism and context – and presents a novel range of approaches to the current discussions that the connections between knowledge, language, action, reasoning, and context continually enlivens. It develops powerful ideas that will push the relevant fields forward and give a sense of the new directions in which mainstream and formal research on knowledge and context is heading.